2019
DOI: 10.25259/jcis-17-2019
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Imaging in Lemmel Syndrome: A Report of Two Cases

Abstract: Lemmel syndrome is a rare and misdiagnosed cause of acute abdominal pain due to a juxtapapillary duodenal diverticulum causing mechanical obstruction of the common bile duct. Frequently, patients suffering from Lemmel syndrome have a history of recurrent access to the emergency room for acute abdominal pain referable to a biliopancreatic obstruction, in the absence of lithiasis nuclei or solid lesions at radiological examinations. Ultrasonography (US) may be helpful in evaluation of upstream dilatation of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 6 publications
3
37
0
1
Order By: Relevance
“…A side-viewing endoscope used during ERCP can help demonstrate the presence of a PAD and is considered the gold standard for diagnosis [2]. Other modalities of imaging, such as a CT scan and magnetic resonance cholangiopancreatography (MRCP), demonstrated that PAD appear as thin-walled cavitary lesions off the medial aspect of the second part of the duodenum [10]. Some PAD can also be filled with fluid, and may resemble pseudocysts, abscesses, or neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…A side-viewing endoscope used during ERCP can help demonstrate the presence of a PAD and is considered the gold standard for diagnosis [2]. Other modalities of imaging, such as a CT scan and magnetic resonance cholangiopancreatography (MRCP), demonstrated that PAD appear as thin-walled cavitary lesions off the medial aspect of the second part of the duodenum [10]. Some PAD can also be filled with fluid, and may resemble pseudocysts, abscesses, or neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…En algunas ocasiones puede llenarse de fluido y confundirse con un absceso pancreático, una neoplasia quística de la cabeza del páncreas o metástasis a los nódulos linfáticos; la estructura del divertículo se observa mejor después de la administración de contraste oral, pudiendo evaluar su tamaño antes y después de la administración, ya que en general su tamaño se duplica, haciendo más evidente la compresión de la vía biliar. El contraste intravenoso es de utilidad para diferenciar tumores biliopancreáticos o pseudoquistes, ya que las paredes del divertículo muestran un leve realce homogéneo (en la fase venosa), después de 45 segundos de su inyección [6][7][8] .…”
Section: Figura 2 Colangiorresonancia Que Muestra Un Divertículo Duodenal (Flecha)unclassified
“…Lemmel syndrome was first defined by Lemmel in 1934 as a diverticulum of the periampullary duodenum causing obstructive jaundice in the absence of choledocholithiasis or neoplasm [1]. The duodenal diverticulum is most commonly a pseudo-diverticulum that is made of a sac-like outpouching of the mucosa and submucosa lacking a complete muscularis layer [2][3][4]. It is mostly found in the second part of the duodenum, 2-3 cm near the ampulla of Vater.…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly found in the second part of the duodenum, 2-3 cm near the ampulla of Vater. With advancing age, the incidence of the periampullary duodenal diverticulum (PAD) increases [3][4]. Up to 22% of cases are incidentally found as they are usually asymptomatic, while less than 10% are complicated with inflammation presenting with obstructive symptoms including abdominal pain and jaundice [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation